HOW TO BE FAIR? OPEN PUBLICATIONS AND RESEARCH DATA AT THE LUBLIN UNIVERSITY OF TECHNOLOGY - KATARZYNA WEINPER; ŁUKASZ TOMCZAK (TASK Quarterly, 2021)
The policy of open access to scientific publications at the Lublin University of Technology gave rise to the issue of sharing research data, which emerged to be a challenge for both research workers and librarians. Promoting awareness in the academic community of how the value and significance of their data increases and when others can make use of it is a novel and challenging task. The objective of this article is to present the activities undertaken for this purpose by the librarians of the Lublin University of Technology. These activities include introducing the Open Access Policy, creating a research data management strategy, and appointing two teams: one with the aim of supporting the University’s Project Office, and the second to create an institutional repository of research data. These actions contribute to the understanding of the value of sharing research results and how to be FAIR when doing so.